2005
DOI: 10.1002/anie.200500114
|View full text |Cite
|
Sign up to set email alerts
|

2,4‐Dinitrobenzenesulfonyl Fluoresceins as Fluorescent Alternatives to Ellman's Reagent in Thiol‐Quantification Enzyme Assays

Abstract: Fluorescent sensor for thiols: Deprotection of nonfluorescent 1 by thiols (R′SH) proceeds rapidly and near‐quantitatively in aqueous solution (pH 7.4) to produce highly fluorescent 2. Assays performed in the presence of 1 provide a rapid and simple method for the determination of inhibitory constants for inhibitors such as donepezil toward acetyl‐ and butyrylcholinesterases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
165
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(176 citation statements)
references
References 23 publications
5
165
0
6
Order By: Relevance
“…9,10 Based on this mechanism, several fluorescent probes for thiolcontaining compounds have been developed. [11][12][13][14] In our recent studies, we observed that other nucleophiles, such as sulfide anion and bisulfite can also lead to the cleavage reaction. Encouraged by this observation, we envisioned that this cleavage reaction might be utilized for the determination of SNH, and such an idea has been attempted in this work by designing a new fluorogenic probe, 4-methylumbelliferyl-2,4-dinitrobenzenesulfonate (4-MUDNBS), for the selective determination of SNH in basic solution.…”
Section: Introductionmentioning
confidence: 97%
“…9,10 Based on this mechanism, several fluorescent probes for thiolcontaining compounds have been developed. [11][12][13][14] In our recent studies, we observed that other nucleophiles, such as sulfide anion and bisulfite can also lead to the cleavage reaction. Encouraged by this observation, we envisioned that this cleavage reaction might be utilized for the determination of SNH, and such an idea has been attempted in this work by designing a new fluorogenic probe, 4-methylumbelliferyl-2,4-dinitrobenzenesulfonate (4-MUDNBS), for the selective determination of SNH in basic solution.…”
Section: Introductionmentioning
confidence: 97%
“…previously Maeda et al, 2005;Shao et al, 2006;Ros-Lis et al, 2004;Tang et al, 2007;Bouffard et al, 2008;Pires and Chmielewski, 2008). In our protocol, a new ligand L could be spontaneously oxidized to a laser dye (coumarin-6) in ambient condition (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fluorescent materials-based assays have several advantages and attractive potentials owing to their intrinsic high sensitivity and real-time monitoring with fast response time. Indeed, along with traditional organic fluorophores (Liu et al, 2012;Maeda et al, 2005), several novel fluorescent nanomaterials such as semiconductor quantum dots (Saa et al, 2010) and DNA templated metal nanoclusters Zhang et al, 2013) have already been utilized to assess AChE activity and screen its inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the determination of AChE activity plays a pivotal role, and the inhibition of AChE with the aim of enhancing ACh levels is effective approach for Alzheimer's disease therapies (Feng et al, 2007). Up to now, the most extensively used assays of activity and inhibition of AChE are, undoubtedly, the traditional and improved Ellman methods (Ellman et al, 1961;Maeda et al, 2005;Miao et al, 2010;Tian et al, 2014). In this regard, by employing the acetylthiocholine (ATCh) or other synthetic thiolesters instead of natural ACh substrate, this series of assays relies on the initial colorimetric, and even following fluorescent, chemiluminescent, and electrochemical methods.…”
Section: Introductionmentioning
confidence: 99%